KERAGAAN 8 GENOTIPE TANAMAN TOMAT (Lycopersicum esculentum Mill.) DI DATARAN RENDAH - Imam, Khairul (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Plant breeding programs aimed to increase the production, one of them with superior varieties. This study aims to obtain genotypes for high yield and tolerance in lowland. The study was conducted from June to October 2013 at faculty of Agriculture Riau University. The experimental design used was Randomized Block Design (RBD), consists of eight genotypes of tomato that IPB 3 x IPB 13, IPB 3 x IPB 64, IPB 3 x IPB 78, IPB 13 x IPB 64, IPB 13 x IPB 78, IPB 64 x IPB 78, Jawara and Fortuna, with 3 replication. Parameters observed are plant height (cm), stem diameter (mm), flowering date (HST), harvesting date (HST), fruit length (cm), fruit diameter (cm), fruit flesh thickness (mm), number of fruit space, weight of 100 seeds (g), number of fruit per plant, weight per fruit (g), weight total per plant (g). The results show variability genotypes tested and the results are different in each genotype. IPB 64 x IPB 78 has a higher yield (weight total per plant, weight per fruit and number of fruit per plant) higher than comparison varieties so that these genotypes can be recommended for furter investigation and  could be released into suitable varietes in low land. Keyword: Performance, tomato, low land